2023
DOI: 10.1002/cnr2.1781
|View full text |Cite
|
Sign up to set email alerts
|

Serum and peritoneal biomarkers for the early prediction of symptomatic anastomotic leakage in patients following laparoscopic low anterior resection: A single‐center prospective cohort study

Abstract: Background Anastomotic leakage (AL) is one of the common complications after rectal cancer surgery. This study aimed to evaluate the combination of biomarkers for the early prediction of symptomatic AL after surgery. Methods A prospective cohort study evaluated the serum and peritoneal biomarkers of patients who underwent laparoscopic low anterior resection (Lap LAR) from November 1, 2021, to May 1, 2022. Multivariate‐penalized logistic regression was performed to explore the independent biomarker with a P‐val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Our study also found that postoperative SII is a strong predictor of DFS in patients after radical resection for rectal cancer, which is consistent with the findings of Zhou et al , who discovered that higher postoperative SII in colorectal cancer patients is associated with shorter survival ( 23 ). In addition, Qi et al found that postoperative SII aids in the early prediction of anastomotic leakage after rectal cancer surgery ( 24 ), which has a negative impact on local recurrence and survival rates after rectal cancer surgery, and early prediction and timely treatment can improve patient outcomes ( 25 ), indicating that postoperative SII has certain predictive value for the prognosis of rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that postoperative SII is a strong predictor of DFS in patients after radical resection for rectal cancer, which is consistent with the findings of Zhou et al , who discovered that higher postoperative SII in colorectal cancer patients is associated with shorter survival ( 23 ). In addition, Qi et al found that postoperative SII aids in the early prediction of anastomotic leakage after rectal cancer surgery ( 24 ), which has a negative impact on local recurrence and survival rates after rectal cancer surgery, and early prediction and timely treatment can improve patient outcomes ( 25 ), indicating that postoperative SII has certain predictive value for the prognosis of rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%